Development Of Augmented Reality Using The Four-D Model In Ipas Learning For Grade 5 Elementary School - Robi’ati Fauziyah; Achmad Noor Fatirul; Hartono (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research aims to develop Augmented Reality (AR) learning media for the IPAS subject on the topic of Harmony in Ecosystems for 5th-grade students at SD Negeri 1 Kedungpring, Lamongan Regency. The research is motivated by low student learning outcomes, with 57% of students not meeting the Minimum Completeness Criteria (KKM), and learning activities that are monotonous with minimal use of interactive digital media. This development research employed the Four-D (4D) model (Define, Design, Develop, Disseminate). The resulting final product is an AR-based teaching module that is interactive, easily accessible, and engaging. The validation results from material experts, design experts, and media experts showed a very good category with an overall average validation score of 4.68 and a validity percentage of 94%. Product trials also indicated a positive response from peers and students. In conclusion, the developed Augmented Reality media is declared feasible/valid and effective in enhancing student motivation and understanding of the IPAS material , while also facilitating teachers in visualizing abstract concepts through interactive three-dimensional objects.